Measuring the concentrations of natural radioactive isotopes and radiation dose rates for Missan Province - Hussein Zarkooshi, Ahmed A. (Iraqi Journal of Physics, 2019)
This research included measuring the concentrations of natural radioactive isotopes U-238 and Th-232 and radiation dose rates for selected areas of Missan province, GR-460 system was used which has the potential to measure the concentrations of natural radioactive isotopes in (ppm) unit and measuring the radiation dose rates in μR/h unit. It was also used with the system the mobile device FH-40 which measures the radiation dose rates in units μSμ/h the measurement results showed the absence of a significant increase in the U-238 and Th-232 concentration where the concentration of isotopes of U-238 and natural Th-232 (3.35-5.46) ppm respectively it is authorized and universally accepted. In terms of radiation dose rates it ranged between 45-65ոSv/հ by GR-460 system and FH-40 device and all these values are within the natural background radiation. Except for one outlying villages that affiliate to the Kahla area were found the radioactive source type 137Cs was left in a swamp of water rancid. Dose rate reached about 6 meters distance from the source 5.3 mSv/h by FH-40 device and GR-460 system 90.6 μR/h where equivalent 815 ոSvհ. The radioactive source has been transferred safely to the main store in AlTuwaitha site.